Arrhythmogenic cardiomyopathy and Brugada syndrome: Diseases of the connexome. Issue 8 (15th February 2014) - Agullo-Pascual, Esperanza; Cerrone, Marina; Delmar, Mario
Abstract : This review summarizes data in support of the notion that the cardiac intercalated disc is the host of a protein interacting network, called "the connexome", where molecules classically defined as belonging to one particular structure (e.g., desmosomes, gap junctions, sodium channel complex) actually interact with others, and together, control excitability, electrical coupling and intercellular adhesion in the heart. The concept of the connexome is then translated into the understanding of the mechanisms leading to two inherited arrhythmia diseases: arrhythmogenic cardiomyopathy, and Brugada syndrome. The cross‐over points in these two diseases are addressed to then suggest that, though separate identifiable clinical entities, they represent "bookends" of a spectrum of manifestations that vary depending on the effect that a particular mutation has on the connexome as a whole.